Use of ofatumumab and eplerenone in post‐transplant recurrence of FSGS. (21st November 2021) - Jain, Namrata G.; Chen, Justin K.; Mahajan, Ruchi; Kehoe, Jacqueline; Singer, Pamela; Whyte, Dilys; Bomback, Andrew S.
Abstract: Background: Focal segmental glomerulosclerosis (FSGS) predisposes patients for risk of recurrent disease in allografts. Methods: We report a case of a recipient of an unrelated living donor renal transplant and discuss considerations for utilization of ofatumumab and eplerenone in treatment for recurrent FSGS. Results: The recipient was initially managed with scheduled plasmapheresis, intravenous immunoglobulin (IVIG), and rituximab post‐transplant during index hospitalization. With notable recurrence of FSGS noted on kidney transplant biopsy, she was initially treated with additional plasmapheresis sessions leading to downtrend in proteinuria. The patient was then transitioned to LDL‐A pheresis, which resulted again in uptrend in proteinuria. This prompted return to scheduled plasmapheresis sessions weekly, leading again to a downtrend in proteinuria. Albumin levels remained within normal range throughout her course. Following initiation of eplerenone and ofatumumab, the patient demonstrated normalization of urine protein:creatinine ratio and remission of FSGS recurrence without need for additional apheresis. Conclusions: With notable risk of recurrence of FSGS in kidney transplants leading to allograft failure, the use of ofatumumab and eplerenone in conjunction should be considered for management to induce remission.